Efficacy and safety of biologics in relapsing polychondritis: a French national multicentre study. Issue 8 (13th March 2018) - Moulis, Guillaume; Pugnet, Grégory; Costedoat-Chalumeau, Nathalie; Mathian, Alexis; Leroux, Gaëlle; Boutémy, Jonathan; Espitia, Olivier; Bouillet, Laurence; Berthier, Sabine; Gaultier, Jean-Baptiste; Jeandel, Pierre-Yves; Konaté, Amadou; et al.
Abstract : Objectives: To assess the efficacy and the safety of biologics in a cohort of patients with relapsing polychondritis (RP). Methods: We conducted a French multicentre retrospective cohort study including patients treated with biologics for RP. Efficacy outcomes were clinical response (partial or complete) and complete response during the first 6 months of exposure, plus daily corticosteroid dose at 6 months. Other outcomes were adverse drug reactions (ADRs), persistence of biologics and factors associated with a response. Results: This study included 41 patients exposed to 105 biologics (tumour-necrosis factor (TNF) inhibitors, n=60; tocilizumab, n=17; anakinra, n=15; rituximab, n=7; abatacept, n=6). Overall response rate during the first 6 months of exposure was 62.9%. Complete response rate was 19.0%. Reduced corticosteroid doses were highly variable among patients. ADRs were mostly infections (n=42). Reasons for biologic withdrawal (73.3%) were insufficient efficacy (34.3%; ranging from 23.5% for tocilizumab to 72.7% for etanercept), loss of efficacy (18.1%) and ADRs (20.9%; mostly for anakinra: 46.7%). Persistence was comparable among biologic classes. Among TNF inhibitors, the highest persistence was observed with adalimumab. Differences in clinical response rates were observed depending on biologics and organ involvement. There were trends towards a lower response rate in cases with associated myelodysplastic syndrome and for a higher response rate for nasal/auricular chondritis, sternal chondritis and concomitant exposure to non-biologic disease-modifying antirheumatic drugs. Conclusions: This study describes the efficacy of biologics for refractory RP. However, the number of complete responses was low and there were concerns about the risk of ADRs, particularly infections.